ANALYSIS OF THE EFFECTIVENESS OF MULTIMODAL ANESTHESIA IN PATIENTS WITH CANCER OF THE BODY OF THE UTERUS DURING HYSTERECTOMY - Босенко, Костянит; Буднюк, Олександр (Modern engineering and innovative technologies, 2024)
The article is devoted to the search for the most effective method of analgesia in patients with cancer of the body of the uterus, to optimize the use of multimodal tactics of anesthetic provision, which would help improve postoperative recovery and redu